Efficiently engineering pore-scale processes: The role of force dominance and topology during nonwetting phase trapping in porous media. (May 2015) - Herring, Anna L.; Andersson, Linnéa; Schlüter, Steffen; Sheppard, Adrian; Wildenschild, Dorthe
Highlights: We investigate residual trapping of nonwetting (NW) phase (air) in sandstone cores. We describe initial air configurations with connectivity metrics. Factors influencing trapping are a function of dominant pore-scale forces. Trapping efficiency decreases as initial air connectivity increases. Pore-scale forces and NW connectivity are important for engineering applications. Abstract: We investigate trapping of a nonwetting (NW) phase, air, within Bentheimer sandstone cores during drainage–imbibition flow experiments, as quantified on a three dimensional (3D) pore-scale basis via x-ray computed microtomography (X-ray CMT). The wetting (W) fluid in these experiments was deionized water doped with potassium iodide (1:6 by weight). We interpret these experiments based on the capillary–viscosity–gravity force dominance exhibited by the Bentheimer–air–brine system and compare to a wide range of previous drainage–imbibition experiments in different media and with different fluids. From this analysis, we conclude that viscous and capillary forces dominate in the Bentheimer–air–brine system as well as in the Bentheimer–supercritical CO2 –brine system. In addition, we further develop the relationship between initial (post-drainage) NW phase connectivity and residual (post-imbibition) trapped NW phase saturation, while also taking into account initial NW phase saturation and imbibition capillary number. We quantify NW phase connectivity via a topological measure as well as by a statistical percolation metric. These metrics are evaluated for their utility and appropriateness in quantifying NW phase connectivity within porous media. Here, we find that there is a linear relationship between initial NW phase connectivity (as quantified by the normalized Euler number, χ ˆ ) and capillary trapping efficiency; for a given imbibition capillary number, capillary trapping efficiency (residual NW phase saturation normalized by initial NW phase saturation) can decrease by up to 60% as initial NW phase connectivity increases from low connectivity ( χ ˆ ≈ 0) to very high connectivity ( χ ˆ ≈ 1). We propose that multiphase fluid-porous medium systems can be efficiently engineered to achieve a desired residual state (optimal NW phase saturation) by considering the dominant forces at play in the system along with the impacts of NW phase topology within the porous media, and we illustrate these concepts by considering supercritical CO2 sequestration scenarios.